A Rare Adverse Effect of Anti-Tumor Necrosis Factor Alpha Therapy: Sarcoidosis - Gönen MENGİ,; Feride GÖĞÜŞ, (Archives of Rheumatology, 2017)
Anti-tumor necrosis factor alpha (anti-TNF-a) therapy has been widely used for the management of rheumatologic diseases. The most frequent adverse effects of anti-TNF-a therapy are infections and malignancies while sarcoidosis is a rare condition. On the other hand, anti-TNF-a therapy has been used in the treatment of sarcoidosis. Elucidation of this paradoxical issue is unclear. In this article, we report an ankylosing spondylitis patient who was diagnosed as sarcoidosis during the period of etanercept usage. Sarcoidosis as a possible adverse effect should be kept in mind during anti-TNF-a therapy.